Analysis of Cellular DNA Content by Flow Cytometry. Issue 1 (13th February 2018) - Darzynkiewicz, Zbigniew; Huang, Xuan; Zhao, Hong
Abstract: Cellular DNA content can be measured by flow cytometry with the aim of : (1) revealing cell distribution within the major phases of the cell cycle, (2) estimating frequency of apoptotic cells with fractional DNA content, and/or (3) disclosing DNA ploidy of the measured cell population. In this unit, simple and universally applicable methods for staining fixed cells are presented, as are methods that utilize detergents and/or proteolytic treatment to permeabilize cells and make DNA accessible to fluorochrome. Additionally, supravital cell staining with Hoechst 33342, which is primarily used for sorting live cells based on DNA‐content differences for their subsequent culturing, is described. Also presented are methods for staining cell nuclei isolated from paraffin‐embedded tissues. Available algorithms are listed for deconvolution of DNA‐content‐frequency histograms to estimate percentage of cells in major phases of the cell cycle and frequency of apoptotic cells with fractional DNA content. © 2017 by John Wiley & Sons, Inc.